The association of parent education and family monthly income on Intelligence Quotient (IQ) among students with special needs in Kelantan, Malaysia - Muhammad Faiz Mohd Ismail,; Ismarulyusda Ishak,; Normah Che Din,; Syarif Husin Lubis,; Nur Zakiah Mohd Saat,; Siti Nor Ismalina Isa, (Penerbit Universiti Kebangsaan Malaysia, 2017)
This paper investigate the effect of parents’ education background and family monthly income on the Intelligence Quotient (IQ) of students with special needs in Kelantan, Malaysia. This cross-sectional method study was employed multistage random sampling to obtain information drawn from 130 participants from 10 selected school in Kelantan, Malaysia. Questionnaire was used to obtain parents’ education background, family monthly income and demographic variables. Students IQ were assessed using Comprehensive Test for Non-Verbal Intelligence (CTONI 2nd Edition). Data analysis involve independent sample t-test, one-way between group ANOVA, Pearson’s correlation and multiple linear regression. From analysis of IQ score, 63.8% of the special needs students scored very poor IQ, 12.3% scored below average and only 1.5% score average IQ. Significant mean difference were revealed between age group (p = 0.002), parents’ education (p = 0.018) and family monthly income (p < 0.05) on special needs students IQ. Post-hoc tukey shows significance between parents who never went to school, went to secondary school (p = 0.037) and university/college (p = 0.021). In term of family monthly income, significance difference were found between family with low and high monthly income (p < 0.05). Family monthly income (r = 0.393, p < 0.01) showed positive moderate correlation on special needs students IQ. After being forwarded by multiple linear regression, it was found that family monthly income (B = 3.605, p < 0.05) and age group of special needs students (B = 0.879, p = 0.002) were significant predictor for IQ score and explained 22.5% of the variance (R2 = 0.225, F (5,124) = 83.94, p < 0.05. Overally, majority of special needs students in current study have very poor IQ score. Further explanation are discussed on the paper.